2008
DOI: 10.1002/ejoc.200800517
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalysed Isomerisation of 2‐Vinylidenehydrofurans to 1,3‐Dienes and Some Aspects of Their Reactivity

Abstract: The transformation of easily accessible 2‐vinylidenehydrofurans into stable 1,3‐dienes has been achieved by using catalytic amounts of palladium(0). These valuable compounds were then engaged in subsequent Diels–Alder reactions giving access to complex heterocyclic cores found in numerous natural products. A rationale for the regioselectivity of the Diels–Alder reactions with vinylfurans has been provided by DFT calculations. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Along with this, it has long been known that furan, thiophene and pyrrole, possessing a conjugated system of double bonds, can also act as a diene moiety. Around 50 years ago, it was found that 2-vinylfurans and 2-vinylthiophenes can play the role of dienes in the intermolecular Diels-Alder reaction, which cleared a short way to benzofuran or benzothiophene derivatives (Paul, 1943;Szmuszkovicz & Modest, 1950;Schmidt, 1953;Scully & Brown, 1953;Davies & Porter, 1957a,b;Kaufmann & Sen Gupta, 1963;Ancerewicz & Vogel, 1993;Drew et al, 2002;Wavrin et al, 2004;Ghobsi et al, 2008). At the end of the last ISSN 2056-9890 century, it was demonstrated that this reaction could be performed in an intramolecular variant when both a heterocyclic diene and a dienophilic moiety are incorporated in the same molecule.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Along with this, it has long been known that furan, thiophene and pyrrole, possessing a conjugated system of double bonds, can also act as a diene moiety. Around 50 years ago, it was found that 2-vinylfurans and 2-vinylthiophenes can play the role of dienes in the intermolecular Diels-Alder reaction, which cleared a short way to benzofuran or benzothiophene derivatives (Paul, 1943;Szmuszkovicz & Modest, 1950;Schmidt, 1953;Scully & Brown, 1953;Davies & Porter, 1957a,b;Kaufmann & Sen Gupta, 1963;Ancerewicz & Vogel, 1993;Drew et al, 2002;Wavrin et al, 2004;Ghobsi et al, 2008). At the end of the last ISSN 2056-9890 century, it was demonstrated that this reaction could be performed in an intramolecular variant when both a heterocyclic diene and a dienophilic moiety are incorporated in the same molecule.…”
Section: Chemical Contextmentioning
confidence: 99%
“…The latter compounds, containing a 2-vinyl-or 2-vinylidene function, are known to undergo a variety of rearrangements including thermal [24][25][26] or palladiumcatalysed [27][28][29]…”
Section: Introductionmentioning
confidence: 99%
“…The isolated oxindole 3aa was subjected to the same reaction conditions. Conversion of 3aa took place smoothly to afford 4aa in 97% yield in 12 h (eq ). , …”
mentioning
confidence: 99%